Some specializations of pitch tournament designs - Finizio, Norman J.; Lewis, Scott J. (Utilitas Mathematica, 1999)
In this study the following four specializations of pitch tournaments are introduced: (1) Z-cyclic pitch tournaments; (2) directed pitch tournaments; (3) multi-pitch tournaments; and (4) pitch tournaments possessing the 5P property. Specific examples of each specialization are given and in some cases infinite classes of such tournaments are presented. Some connections with other combinatorial structures are also established.